Restorative Mechanism of Neural Progenitor Cells Overexpressing Arginine Decarboxylase Genes Following Ischemic Injury - Kim, Jae Young (Exp Neurobiol, 2019)
Cell replacement therapy using neural progenitor cells (NPCs) following ischemic stroke is a promising potential therapeutic strategy, but lacks efficacy for human central nervous system (CNS) therapeutics. In a previous in vitro study, we reported that the overexpression of human arginine decarboxylase (ADC) genes by a retroviral plasmid vector promoted the neuronal differentiation of mouse NPCs. In the present study, we focused on the cellular mechanism underlying cell proliferation and differentiation following ischemic injury, and the therapeutic feasibility of NPCs overexpressing ADC genes (ADC-NPCs) following ischemic stroke. To mimic cerebral ischemia in vitro , we subjected the NPCs to oxygen-glucose deprivation (OGD). The overexpressing ADC-NPCs were differentiated by neural lineage, which was related to excessive intracellular calcium-mediated cell cycle arrest and phosphorylation in the ERK1/2, CREB, and STAT1 signaling cascade following ischemic injury. Moreover, the ADC-NPCs were able to resist mitochondrial membrane potential collapse in the increasingly excessive intracellular calcium environment. Subsequently, transplanted ADC-NPCs suppressed infarct volume, and promoted neural differentiation, synapse formation, and motor behavior performance in an in vivo tMCAO rat model. The results suggest that ADC-NPCs are potentially useful for cell replacement therapy following ischemic stroke.